8. IMPLEMENTASI SERTIFIKASI MASSAL SWADAYA DI KABUPATEN KUDUS PERIODE 2006-2008 - Utomo, Susilo; Harsasto, Priyatno; Purwoko, Purwoko (FORUM, 2009)
This research aims at scrutinizing the implementation of self-mass sertification (SMS) and the difficulties during its implementation in Kudus Regency in the period of 2006-2008. the researcher employes descriptive qualitative method and indept interview to collect relevant data. There are three important findings :Firstly, SMS’s procedures are much simpler, easier and cheaper tahn the conventional’s procedures; secondly, they who want to certify their land have to pay only small of money, cheaper than conventional’s procedure;  and thisrdly, the constraint of the implementation comes from its mass characteristic as well as the lack of socialization of the program.